Enhancing Human Capital and Leadership in Public Administration: Training, Growth, and Retention Strategies - Fedotova, Tatyana; Shevchenko, Yaroslav; Romanenko, Kateryna; Nunyuk, Inna; Khairulin, Oleg (My University, 2025)
Several differences from traditional practices in the private sector characterise public human capital management. The processes of staff development and retention are more complex, given the peculiarities of financing professional training of employees, which depends on the state of the budget, the flexibility of the personnel system and the methods of development and incentives for specialists. In the context of growing uncertainty, there are difficulties in retaining staff in the public service. This article aims to empirically study the state of human capital and leadership management in public administration in Ukraine. The article uses a descriptiveanalytical design, analysing secondary data from the National Agency of Ukraine on Civil Service survey on the state of organisational culture and professional development of civil servants in 2023. To assess the state of investment in human capital management, the amount of funding for professional training of civil servants in Ukraine for 2018–2024 is estimated. The study results indicate the prevalence of traditional ways of developing and retaining civil servants in Ukraine, which include acquiring qualifications, professional training, education and experience. Therefore, public administration’s human capital management system remains underdeveloped in terms of its flexibility and adaptability to changing, complex environmental conditions. Civil servants consider salary and increased responsibility to be prerequisites for professional development, and professional knowledge, personal experience, and personal moral qualities are factors of career growth. External factors affecting the state of human capital in Ukraine have a weak impact on its development. Increasing the level of remuneration of civil servants meets their personal needs. At the same time, it is important to develop human capital management strategies with measurable results for their external motivation. The practical value of the study is to highlight the state of human capital management in Ukraine.
Keywords: Public and political administration; Professional training; Uncertainty; Vital activity; Gamification